Henoch schonlein purpura in pregnancy: a lesser known phenomenon - Chakrabarti, Salil Bindu; Tigga, Maureen Prativa; Ray, Jayanta; Debbarma, Amulya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Henoch Schonlein Purpura is a rare disease and its occurrence during pregnancy is exceptional. Very little information is found in the literature regarding this topic and only handful of case reports are available to throw light upon the same. Presented here is a case of a 30 year old primigravida with pre-existent disease with successful fetomaternal outcome subsequently.